2022
DOI: 10.3390/nu14040746
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Maternal Obesity Are Associated with Increased Oxidative Stress in Newborns: A Cross-Sectional Study

Abstract: Overweight and obesity have become a world-health public problem, mainly for developing countries. Both health conditions have a higher prevalence among women of childbearing age. Physiopathology, overweight and obesity are characterized by a chronic oxidative stress status, which has deleterious effects on mothers and children. Hence, we determine whether the qualities of diet during pregnancy and maternal pregestational body mass index (BMI) are associated with increased oxidative stress markers in mothers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…We observed that the 8-OHdG levels in mothers and newborns correlated strongly ( Figure 2 ), which is in accordance with our previous study of another OS marker [ 39 ]. The source of 8-OHdG in pregnant women and newborns has not been identified yet [ 52 ], but Fukushima et al showed that placental tissue stained positive for 8-OHdG [ 53 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We observed that the 8-OHdG levels in mothers and newborns correlated strongly ( Figure 2 ), which is in accordance with our previous study of another OS marker [ 39 ]. The source of 8-OHdG in pregnant women and newborns has not been identified yet [ 52 ], but Fukushima et al showed that placental tissue stained positive for 8-OHdG [ 53 ].…”
Section: Discussionsupporting
confidence: 92%
“…A food frequency questionnaire to assess regular food intake was administered by a trained doctor to all participants in the third trimester before labour, as previously described [ 39 ]. The questionnaire was validated for estimated folate intake in the Mexican population.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent cross‐sectional study involving 242 mother‐newborn pairs, levels of oxidative stress markers (malondialdehyde and nitric oxide) in plasma from cord blood at birth were higher in mother‐newborn pairs with maternal obesity than those with normal weight. Meaningfully, a higher intake of fruit and vegetables during pregnancy was negatively correlated with the levels of oxidative stress markers 136 . Consistently, another study in nonhuman primates also reported that maternal WSD induces oxidative stress in hepatic stellate cells and myofibroblasts of fetuses 44 .…”
Section: Other Mechanisms Involved In Maternal Obesity and Offspring ...mentioning
confidence: 55%
“…Meaningfully, a higher intake of fruit and vegetables during pregnancy was negatively correlated with the levels of oxidative stress markers. 136 Consistently, another study in nonhuman primates also reported that maternal WSD induces oxidative stress in hepatic stellate cells and myofibroblasts of fetuses. 44 Alleviation of oxidative stress in the fetal livers holds the promise for halting hepatic steatosis and fibrosis via supplementation of resveratrol in WSD.…”
Section: Oxidative Stressmentioning
confidence: 59%
“…Fiber has usually been associated with beneficial outcomes in pregnancy. The studies by López-Yáñez [ 67 ] and Kim [ 68 ] found that pregnant women with MDA concentrations in the highest tertiles had a lower consumption of high-fiber foods, such as fruits and vegetables, than those in the lowest tertile. The Australian Longitudinal Study for Women’s Health showed that women in the highest quartile of pre-pregnancy fiber intake had a 33% lower risk of GDM compared to women in the lowest quartile.…”
Section: Discussionmentioning
confidence: 99%